Design Studio Pedagogy: A Comparative Study of Teaching Approaches - Al-Ayash, Aseel A. (Dirasat: Human and Social Sciences, 2025)
Objectives: This study presents a comparative analysis of various teaching methodologies within design studio instruction, focusing on their impact on student learning outcomes, creativity, and problem-solving skills. Methods: Utilizing both quantitative and qualitative research methods, the study includes a student survey and interviews with faculty members. Results: The results, derived from a comprehensive survey of 100 students from universities in Bahrain, reveal a positive perception of design studios. Interviews with instructors highlight the strengths and challenges inherent in different teaching methods. Traditional lectures are effective in conveying fundamental knowledge, whereas project-based learning, design thinking, collaborative learning, and experiential learning prioritize hands-on experiences, real-world applications, and innovation. Conclusion: The study identifies challenges such as technological issues and resource constraints, and proposes tailored teaching methods, enhanced engagement, resource provision, and professional development as mitigation strategies. This research provides valuable insights into the effectiveness of various educational approaches and offers recommendations for improving design studio education and addressing challenges to enhance the overall educational experience.